Impaired Postprandial Adipose Tissue Blood Flow Response Is Related to Aspects of Insulin Sensitivity - Fredrik Karpe; Barbara A. Fielding; Vera Ilic; Ian Macdonald; Lucinda K. M. Summers; Keith N. Frayn (2002)
Obesity has been associated with dysfunctional postprandial adipose tissue blood flow (ATBF), but it has also been recognized that the interindividual response is highly variable. The present work aimed at characterizing this variability. Fifteen subjects were given 75 g oral glucose, and abdominal subcutaneous ATBF was monitored by the 133Xe washout method. Determinants of insulin sensitivity based on nonesterified fatty acid (NEFA) suppression after oral glucose administration [ISI(NEFA)] were higher in the top tertile ATBF response group (1.29 ± 0.09 vs. 0.90 ± 0.08 in the lower tertiles, P = 0.01). ISI(NEFA) was related to ATBF response (rs = 0.73, P < 0.002) as well as insulin sensitivity based on postprandial glycemia [ISI(gly), rs = 0.58, P < 0.05], whereas the homeostasis model assessment (HOMA) index (rs = −0.39, P = 0.16) was not. The relationship between increase in ATBF and ISI(NEFA) was independent of BMI (P = 0.015) in multivariate analysis. Subjects with a high ATBF response had significantly higher increase of plasma norepinephrine (P < 0.05), indicating a link between postprandial insulinemia, sympathetic activation, and ATBF response. There is a close relationship between insulin sensitivity and the regulation of postprandial ATBF, independent of adiposity. Impaired regulation of ATBF seems to be another facet of the insulin resistance syndrome.